Migration of Energy Production to Nuclear Fusion - Glickman, Lucas (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
In stellar bodies, its gravitational force pushes atoms together fusing them, causing Nuclear Fusion to occur, so that the extra mass is converted into pure energy by Albert - Einstein’s E = mc2 mass-energy equivalence formula. On Earth, temperatures around 150 million degrees Celsius (average particle kinetic energy around 10 keV) are required to overcome Coulomb’s law, the force between two charged particles, so that the fusion can occur. The preferred fuel source is Helium-3, found in abundance on the moon, due to its clean nature and energy output. In the future, Nuclear Fusion could play a role as the main form of electricity production once the proper infrastructure is built.